(untitled) (Journal of Parents and Teachers, 2013)
Music is a very important element in pre-school education. It is given a little importance from educational institutions and printing houses although music is in every area in pre-school education. Music can be the leitmotif to get all these areas together. Especially in pre-school education, music helps to develop not only fine motor skills but gross motor skills, audition, movement, self knowledge, autonomy and oral expression. A suggestion to printing houses to make music an important subject in pre-school education is made.